Adolescent Sexual and Reproductive Health Services and Implications for the Provision of Voluntary Medical Male Circumcision: Results of a Systematic Literature Review. - Michelle R Kaufman; Marina Smelyanskaya; Lynn M Van Lith; Elizabeth C Mallalieu; Aliza Waxman; Karin Hatzhold; Arik V Marcell; Susan Kasedde; Gissenge Lija; Nina Hasen; Gertrude Ncube; Julia L Samuelson; et al. (PLoS ONE)
Background Voluntary medical male circumcision (VMMC) is a critical HIV prevention tool. Since 2007, sub-Saharan African countries with the highest prevalence of HIV have been mobilizing resources to make VMMC available. While implementers initially targeted adult men, demand has been highest for boys under age 18. It is important to understand how male adolescents can best be served by quality VMMC services. Methods and findings A systematic literature review was performed to synthesize the evidence on best practices in adolescent health service delivery specific to males in sub-Saharan Africa. PubMed, Scopus, and JSTOR databases were searched for literature published between January 1990 and March 2014. The review revealed a general absence of health services addressing the specific needs of male adolescents, resulting in knowledge gaps that could diminish the benefits of VMMC programming for this population. Articles focused specifically on VMMC contained little information on the adolescent subgroup. The review revealed barriers to and gaps in sexual and reproductive health and VMMC service provision to adolescents, including structural factors, imposed feelings of shame, endorsement of traditional gender roles, negative interactions with providers, violations of privacy, fear of pain associated with the VMMC procedure, and a desire for elements of traditional non-medical circumcision methods to be integrated into medical procedures. Factors linked to effective adolescent-focused services included the engagement of parents and the community, an adolescent-friendly service environment, and VMMC counseling messages sufficiently understood by young males. Conclusions VMMC presents an opportune time for early involvement of male adolescents in HIV prevention and sexual and reproductive health programming. However, more research is needed to determine how to align VMMC services with the unique needs of this population.